Brief Report: Characteristics and Needs of Persons Admitted to an Inpatient Psychiatric Hospital With Workers' Compensation Coverage - Herring, Mary Grace; Martin, Lynn; Kristman, Vicki L. (Frontiers in Psychiatry, 2021)
The rise of mental health issues in the workplace is widely known. Though mental health issues were not covered by the Workplace Safety Insurance Board (WSIB) in Ontario (Canada) until 2018, it was listed as responsible for payment of inpatient psychiatric hospital stays between 2006 and 2016. This population-level observational analytic study compares the clinical and service needs of 1,091 individuals admitted to inpatient psychiatry with WSIB coverage to all other admissions (n=449,128). Secondary analysis was based on the interRAI Mental Health assessment. The WSIB group differed from all other admissions on almost all characteristics considered. Most notably, depression (65.08% vs. 57.02%), traumatic life events (25.48% vs. 15.58%), substance use (58.02% vs. 46.92%), daily pain (38.31% vs. 12.15%) and sleep disturbance (48.95% vs. 37.12%) were much higher in the WSIB group. Females with WSIB coverage had more depression (74.36% vs. 59.91%) and traumatic life events (30.00% vs. 22.97%), whereas males had more substance issues (63.62% vs. 47.95%). In addition, persons under the age of 55 had more substance issues (< 25=75.47%; 25-54=61.64%: 55+=40.54%) and traumatic life events (<25=26.41%; 25-54=28.18%; 55+=15.31%), while those 25-54 years had more daily pain (41.67% vs. <25=3.77% and 55+=34.23%) and sleep disturbance (50.74% vs. <25=33.96% and 55+=45.94%). All variables differed significantly by sex and age within the comparison group, though not always following the patterns observed in the WSIB group. Future research examining mental health needs and outcomes among injured workers receiving inpatient psychiatric services is needed, and should take into account sex and age.